2019
DOI: 10.3390/rs11060609
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Wetland Types in Semiarid Floodplains: A Statistical Learning Approach

Abstract: Detailed vegetation maps are needed for wetland conservation and restoration as different vegetation communities have distinct water requirements. It is a continuous challenge to map the distribution of different wetland types on a regional scale, and a trade-off between the categorical details and availability of resources to ensure broad applications is often necessary for operational mapping. Here, we evaluated the capacity and performance of statistical learning in discriminating wetland types using Landsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…The original map discriminates wetlands into 13 major groups based on dominant plant species. Since large-scale wetland classification with satellite imagery has practical limitations to the number of classes [45], we aggregated the 13 groups into five broad wetland types based on the vegetation structure and the salinity; including three freshwater types (i.e., forested wetland, shrubland wetland, and grassy wetland) and two saline wetlands (i.e., mangrove and saltmarsh). In addition, we randomly sampled 2888 points from other land covers using the land use/land cover map of NSW (NSW Landuse 2017, downloaded on 12 August 2019 from https://data.nsw.gov.au/data/dataset/nsw-landuse-2017) as "background" points.…”
Section: Wetland Mapmentioning
confidence: 99%
See 2 more Smart Citations
“…The original map discriminates wetlands into 13 major groups based on dominant plant species. Since large-scale wetland classification with satellite imagery has practical limitations to the number of classes [45], we aggregated the 13 groups into five broad wetland types based on the vegetation structure and the salinity; including three freshwater types (i.e., forested wetland, shrubland wetland, and grassy wetland) and two saline wetlands (i.e., mangrove and saltmarsh). In addition, we randomly sampled 2888 points from other land covers using the land use/land cover map of NSW (NSW Landuse 2017, downloaded on 12 August 2019 from https://data.nsw.gov.au/data/dataset/nsw-landuse-2017) as "background" points.…”
Section: Wetland Mapmentioning
confidence: 99%
“…Many performance metrics or measures, such as Log-Loss, kappa coefficient, producer's and user's accuracy, and AUC, are given in the literature with the aim of providing a better measure of mapping accuracy [82]. Among these metrics, overall and individual class accuracies derived from the error matrix are the simplest, therefore have been widely used to evaluate model performance (e.g., References [45,83]). The kappa coefficient, which measures the difference between the actual agreement in a confusion matrix and the chance agreement, provides a better measure for the accuracy of a classifier than the overall accuracy as it takes into account the whole confusion matrix rather than the diagonal elements alone [84].…”
Section: Performance Metrics For Classification Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of all three employed methods (i.e., elbow, gap statistic, and average silhouette) suggested that our approach might not be consistent for finer (i.e., above three classes) clustering. Powell et al [42] suggested that discrimination limit for semi-arid floodplain using Landsat based NDVI metrics was four classes, beyond which the performance was significantly deteriorated.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted based on remote sensing both at regional and global scale to analyze the wetlands changes (Pham-Duc et al, 2017;Aires et al, 2018;Wohlfart et al, 2018;Li et al, 2019;Powell et al, 2019). Microwave datasets have an advantage of not being affected by the cloud cover with higher sensitivity to detect inundation changes (Schroeder et al, 2015).…”
Section: Introductionmentioning
confidence: 99%